Image-based promoter prediction: a promoter prediction method based on evolutionarily generated patterns. Issue 1 (December 2018) - Wang, Sheng; Cheng, Xuesong; Li, Yajun; Wu, Min; Zhao, Yuhua
Abstract Prediction of promoter regions is crucial for studying gene function and regulation. The well-accepted position weight matrix method for this purpose relies on predefined motifs, which would hinder application across different species. Here, we introduce image-based promoter prediction (IBPP) as a method that creates an "image" from training promoter sequences using an evolutionary approach and predicts promoters by matching with the "image". We usedEscherichia coli σ70 promoter sequences to test the performance of IBPP and the combination of IBPP and a support vector machine algorithm (IBPP-SVM). The "images" generated with IBPP could effectively distinguish promoter from non-promoter sequences. Compared with IBPP, IBPP-SVM showed a substantial improvement in sensitivity. Furthermore, both methods showed good performance for sequences of up to 2, 000 nt in length. The performances of IBPP and IBPP-SVM were largely affected by the threshold and dimension of vectors, respectively. The source code and documentation are freely available athttps://github.com/hahatcdg/IBPP .